Numerical Investigation on the Performance Enhancement of InGaN/GaN Light-Emitting Diodes with a Novel p-i-n Electron-Blocking Layer - Jun Wang; Tian Wang (International Journal of Optics)
In this study, we propose a novel p-i-n AlGaN electron-blocking layer for GaN-based LEDs. The aim is to enhance the confinement of electrons and improve the efficiency of hole injection, ultimately resulting in a significant enhancement in LED performance. Detailed simulations and analysis were conducted to compare the performances of GaN-based LEDs with a conventional EBL and our proposed EBL. It was observed that our newly proposed p-i-n AlGaN EBL significantly outperforms the conventional EBL in terms of output power and efficiency across a wide range of injecting currents. These improvements can be attributed to the strong reverse electrostatic field induced by our proposed p-i-n AlGaN EBL, which not only enhances electron confinement but also improves hole injection efficiency.